Factors associated with congenital syphilis: A retrospective study in Jiangxi Province, China. (February 2022) - Wan, Zhihua; Tao, Yuling; Zhang, Huan; Hu, Yang; Shu, Kuanyong
Background: There are a lack of studies about factors influencing congenital syphilis (CS) in economically underdeveloped areas, such as Jiangxi Province, China. Methods: A retrospective study was conducted based on the information system of prevention of mother-to-child transmission of syphilis management in Jiangxi Province, China. Pregnant women with syphilis infection who delivered ≥28 gestational weeks and registered in this system from 1 January 2013 to 2030 June 2018 were enrolled. Maternal characteristics and treatment regimens associated with CS were evaluated using multivariable regression analysis. Results: 1196 syphilis infected mothers and their 1207 infants were included in the analyses, and 116 infants were diagnosed with CS, providing an overall incidence of 9.61% (116/1207). Multivariable logistic regression analysis showed that increasing maternal age was barely associated with the risk of CS (adjusted odds ratio (aOR) = 0.97, 95% CI, 0.93–1.00, p = .047). Women with a high nontreponemal serum test titer (≥1:8) had a 126% increased risk of delivering an infant with CS than those with a low titer (<1:8) (aOR = 2.26, 95% CI, 1.51–3.39, p < .001). The risk for CS decreased significantly in infants born to mothers receiving adequate treatment than those receiving no treatment (aOR = 0.36, 95% CI, 0.21–0.61, p < .001). Conclusions: Adequate treatment is critical for the prevention of CS. Further strategies focusing on early diagnosis and adequate treatment among syphilis infected pregnant women, particularly among those with younger age and high nontreponemal titer, should be strengthened to prevent CS.